(untitled) (Jurnal Arsitektur ARCADE, 2026)
Research on co-working spaces has predominantly focused on commercial settings, while studies employing an environmental psychology approach in academic co-working spaces in Indonesia remain limited. This study aims to evaluate user satisfaction in the co-working spaces of the Smart Green Learning Center (SGLC), Universitas Gadjah Mada, based on environmental psychology dimensions. A quantitative-descriptive approach was employed involving 240 respondents across 25 co-working space units. Data were collected through a questionnaire covering environmental control, thermal comfort, visual comfort, acoustics and privacy, spatial flexibility, and social perception. Data were analyzed using descriptive statistics and supported by users’ open-ended responses. The results indicate that overall user satisfaction was very high, with a mean score of 4.26. Spatial flexibility achieved the highest score (4.37), followed by visual comfort (4.22) and social perception (4.20), while acoustics and privacy received the lowest score (3.57). In addition, 26.3% of respondents reported experiencing thermal discomfort while using the spaces. These findings suggest that the quality of user experience in academic co-working spaces is influenced by the interaction of physical, psychological, and social aspects of the environment. The study highlights the importance of an environmental psychology approach in the design and evaluation of collaborative learning spaces in higher education settings.